2018
DOI: 10.1371/journal.pone.0194834
|View full text |Cite
|
Sign up to set email alerts
|

Neochloris oleoabundans is worth its salt: Transcriptomic analysis under salt and nitrogen stress

Abstract: Neochloris oleoabundans is an oleaginous microalgal species that can be cultivated in fresh water as well as salt water. Using salt water gives the opportunity to reduce production costs and the fresh water footprint for large scale cultivation. Production of triacylglycerols (TAG) usually includes a biomass growth phase in nitrogen-replete conditions followed by a TAG accumulation phase under nitrogen-deplete conditions. This is the first report that provides insight in the saline resistance mechanism of a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 88 publications
1
26
0
1
Order By: Relevance
“…However, the disrupted microalgae added to the systems contained other biomolecules, such as pigments, lipids, carbohydrates and other proteins apart from Rubisco. The overall composition of microalgae is influenced by cultivation conditions . Microalgae cultivated in freshwater has higher amount of proteins and pigments than microalgae cultivated under saline conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the disrupted microalgae added to the systems contained other biomolecules, such as pigments, lipids, carbohydrates and other proteins apart from Rubisco. The overall composition of microalgae is influenced by cultivation conditions . Microalgae cultivated in freshwater has higher amount of proteins and pigments than microalgae cultivated under saline conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The overall composition of microalgae is influenced by cultivation conditions. 53 Microalgae cultivated in freshwater has higher amount of proteins and pigments than microalgae cultivated under saline conditions. When using N. oleoabundans cultivated in freshwater more proteins were concentrated in the interface [ Fig.…”
Section: Protein Partitioning In Atpssmentioning
confidence: 99%
“…According to (Rao et al, 2007), high salinity can stimulate accumulation of intracellular lipids in microalgae. In a recent study dealing with Neochloris oleoabundans under salt and nitrogen stress, it has been shown that proline and the ascorbate-glutathione cycle play a key role for successful osmoregulation under salt stress; furthermore two genes such as glycerol-3-phosphate acyltransferase and glycerol-3-phosphate dehydrogenase where identified as promising targets to enhance TAG production (de Jaeger et al, 2018). Hence a possible explanation of our results is that under the stresses studied in S. dimorphus glycerol-3-phosphate dehydrogenase and glycerol-3-phosphate dehydrogenase are regulated in a way that the carbohydrate accumulation is reduced while lipid accumulation is stimulated as shown in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of antioxidant enzymes, osmolytes, and osmoprotectant molecules has been reported in Neochloris oleoabundans and Chlorella sp. S30, when cultivated under NaCl stress [15, 17].…”
Section: Introductionmentioning
confidence: 99%